Mother-baby interaction at home. An observational study with 9-month-old babies in reading situations and other daily routines - Mareovich, Florencia (2024)
Shared book reading is a very common activity during early childhood. However, few researches analyze reading sessions with babies under one-year of age. This study aims to describe and compare mothers’ interaction styles with their 9-month-old babies during reading and daily routines at home (such as bathing, playing, or feeding). Findings show that mothers tend to adopt a more dialogical style during reading and a more direct approach during day-to-day activities. Babies mostly perform manipulative actions on books. In response to maternal interventions, infants respond in a more contingent and conventional way. Results suggest that mothers play a significant role in structuring shared reading experiences within the first year of life, supporting the recommendation to increase reading at early ages.